The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/2047487317736828
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation is associated with higher prevalence of cardiovascular disease risk-factors among Chinese immigrants in Australia: Evidence from a large population-based cohort

Abstract: Background Acculturation is associated with increased prevalence of cardiovascular disease (CVD) risk-factors among immigrants in Western countries. Little is known about acculturation effects on CVD risks among Chinese immigrants, one of the fastest growing populations in Western countries. In this study, we aim to examine the association between acculturation and CVD risk-factors among Chinese immigrants, Australia's third-largest foreign-born group. Methods We accessed a subsample of Chinese immigrants ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 38 publications
5
57
1
2
Order By: Relevance
“…High blood pressure was defined as an SBP of ≥130 mmHg and/or DBP of ≥85 mmHg. Finally, we calculated the total number of adverse cardiometabolic risk factors as the sum of each adverse risk factor, and defined high risk as having ≥three adverse cardiometabolic risk factors [20,21].…”
Section: Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…High blood pressure was defined as an SBP of ≥130 mmHg and/or DBP of ≥85 mmHg. Finally, we calculated the total number of adverse cardiometabolic risk factors as the sum of each adverse risk factor, and defined high risk as having ≥three adverse cardiometabolic risk factors [20,21].…”
Section: Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…While cross-sectional studies have reported higher CVD risk and poor cardiovascular profiles in more acculturated second-generation (born in host country) individuals compared to less acculturated foreign-born immigrants 16 23 , the observed generational variations do not provide an estimate of the “true” generational effect on health, as they may be confounded by secular trends in the health of immigrants. Currently, longitudinal data on the impact of generational changes on the incidence of CVD and its risk factors in immigrant populations, particularly from Asian cultures, are rare.…”
Section: Introductionmentioning
confidence: 89%
“…The immigration processes, actively ongoing in many regions of the world, also represent a social risk factor for the development of cardiovascular diseases and the significance of this risk factor became a subject of studies recently. For example, the studies showed that the prevalence of cardiovascular risk factors among Chinese immigrants in Australia is associated with the process of cultural assimilation [51]. A likelihood of hypertension что женщины имели повышенный риск назначений неподходящих препаратов по сравнению с мужчинами по критериям EU(7)-PIM, но у мужчин риск был выше, чем у женщин по критериям Бирса.…”
Section: социальные факторы и предикторы ссзunclassified
“…Иммиграционные процессы, активно протекающие во многих регионах мира, представляют собой еще один социальный фактор развития ССЗ, значимость которого стали изучать сравнительно недавно. Например, было показано, что в Австралии распространенность сердечно-сосудистых факторов риска среди иммигрантов из Китая ассоциирована с процессом культурной ассимиляции [51]. В сравнении с азиатами, рожденными в Австралии, вероятность того, что мигранты из Северо-Восточной Азии имеют гипертонию и/или гиперхолестеринемию, на 20-30% ниже; вероятность диабета у мигрантов из Юго-Восточной Азии на 46-46% выше.…”
Section: социальные факторы и предикторы ссзunclassified